(3GdQjGVjGJ h GdHQeLI GdNWjI h JWHjbGJgG GdGOGQjI h GdGbJUGOjI (B/s - (3GdHQhGQj, CfeGQ Cejfs; (3OGhO, YQHjI YHO GdQMefs ((3YeGf(B: s (3OGQ eLOdGhj(B, s, 2011)
(3GdeLehYGJ , GdeYGOdGJ hGdOhGd h JWHjbGJgG GdGOGQjI h GdGbJUGOjI , LHQ GdeUahaGJ h GdJaGVd h GdJcGed h GdHQeLI GdNWjI h fXQjI GdeHGQGI h JWHjbGJgG GdGOGQjI h GdGbJUGOjIs
Keywords: (3GdEOGQIs; (3GdEbJUGO GdQjGVjs; (3GdHQeLjGJs; (3GdQjGVjGJs; (3Yde GdMGShHs